The impact of blockchain on the aviation industry: Findings from a qualitative study. (December 2021) - Pinto Lopes, Daniel; Rita, Paulo; Treiblmaier, Horst
Abstract: The aviation industry is searching for innovative solutions to boost its business in a sector that operates on a financial knife-edge driven by fierce competition. This paper seeks to identify how blockchain, an immutable and append-only data ledger, can impact the aviation industry. This study presents the results from 18 interviews with industry experts. Text mining and a thematic data analysis were combined to investigate the likelihood of the airline industry adopting a disruptive technology that has the potential to affect various stakeholders and replace current platforms. The connection between the key terms and emergent themes is visualised and discussed in detail. The current attitude as well as the expectations and uncertainties of the aviation industry towards blockchain are systematised. The five core topics determining the adoption of blockchain by the industry are specific adoption factors, the replacement of current centralised platforms, customer loyalty, adoption barriers and a general lack of awareness. All topics are discussed in detail, and concrete propositions for future academic research are put forward.